2022
DOI: 10.3389/fchem.2022.880884
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of 3DOM ZrTiO4 Support, WxCeMnOδ/3DOM ZrTiO4 Catalysts, and Their Catalytic Performance for the Simultaneous Removal of Soot and NOx

Abstract: As an efficient and durable engine, a diesel engine has a broad application. However, soot particles (PM) and nitrogen oxides (NOx) coming from diesel engines are the main causes of air pollution, so it is necessary to design and prepare an effective catalyst for the simultaneous elimination of PM and NOx. In this work, a novel 3DOM ZrTiO4 support and a series of WxCeMnOδ/3DOM ZrTiO4 catalysts (where x indicates the wt% of W) were designed and fabricated by the colloidal crystal template technique. Among the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…In addition to the metal oxides with porous structures mentioned above, catalysts with supported 3DOM structures have been used for simultaneous PM and NO x elimination. In our group, Wang et al 440 synthesized a series of W x CeMnO δ / 3DOM ZrTiO 4 catalysts using 3DOM ZrTiO 4 as a carrier and investigated the mechanism of simultaneous PM and NO x elimination by the catalysts, as shown in Figure 27G. The results indicated that, during the PM elimination process, 3DOM W 1 CeMnO δ /3DOM ZrTiO 4 catalyst generates more active oxygen species.…”
Section: Application Of Pore-structured Metal Oxide Catalysts For Sim...mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the metal oxides with porous structures mentioned above, catalysts with supported 3DOM structures have been used for simultaneous PM and NO x elimination. In our group, Wang et al 440 synthesized a series of W x CeMnO δ / 3DOM ZrTiO 4 catalysts using 3DOM ZrTiO 4 as a carrier and investigated the mechanism of simultaneous PM and NO x elimination by the catalysts, as shown in Figure 27G. The results indicated that, during the PM elimination process, 3DOM W 1 CeMnO δ /3DOM ZrTiO 4 catalyst generates more active oxygen species.…”
Section: Application Of Pore-structured Metal Oxide Catalysts For Sim...mentioning
confidence: 99%
“…Copyright 2021 The Authors. Published by American Chemical Society), (G) W x CeMnO δ /3DOM ZrTiO 4 (Reprinted with permission under Creative Commons CC-BY 4.0 license from ref . Copyright 2022 The Authors), (H) Mn x Co 1– x O δ /3DOMm Ti 0.7 Si 0.2 W 0.1 O y (Reprinted with permission from ref .…”
Section: Application Of Porous Metal Oxide Catalysts For Catalytic Pu...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although an SCR catalyst can be coated onto a DPF to form an integrated unit (referred to as SCRF [7], SCRoF [8] or SPDF [9]), the filter still requires active regeneration by the injection of fuel into an upstream DOC. Therefore, the challenge remains to design a catalysed filter in which the chemistry of NOx-reduction is coupled with that of continuous soot oxidation [10] (e.g., using perovskites [11] or 3DOM mixed-metal oxides [12]), so avoiding the requirement for intermittent regeneration of the filter. We have previously shown [13,14] that catalysts based on Ag/CZA (silver supported on ceria-zirconia-alumina), in which the functions of incomplete NOx reduction and soot oxidation are combined, have the potential to control soot particulate and NOx emissions at the low temperatures typical of the exhaust gas emitted by the engine of a diesel passenger car.…”
Section: Introductionmentioning
confidence: 99%